Guidance for CRP-Commissioned External Evaluations (CCEEs) - CGIAR Independent Evaluation Arrangement (CGIAR Independent Evaluation Arrangement, 2015)
This Guidance is intended as a helpful reference document for those commissioning and carrying out CRP-Commissioned External Evaluations, with the aim of raising quality in evaluation reports across CRPs.